The cell-based approach of hemostasis, coagulopathy, and the implications for the pediatric cardiac anesthesiologist - Munlemvo, Dolly M. (Frontiers in Anesthesiology, 2025)
Newborns and infants undergoing complex heart surgery often encounter post-operative bleeding episodes and coagulopathy following cardiopulmonary bypass (CPB). Addressing these challenges necessitates a comprehensive understanding of the intricate mechanisms involved, including thrombin generation, platelet activation, fibrinolysis, and the pivotal role of fibrinogen. This article explores these critical components within the context of pediatric patients undergoing cardiac surgery with CPB, drawing from Hoffman and Monroe's cell-based coagulation approach. By shedding light on these key aspects, we aim to equip clinicians with essential insights for designing a well-guided patient blood management strategy in this type of surgery.